A short review of ciraparantag in perspective of the currently available anticoagulant reversal agents. Issue 10 (October 2022) - Leentjens, J.; Middeldorp, S.; Jung, C.
Highlights: Ciraparantag is a promising new universal anticoagulant reversal agent currently being investigated in a phase 3 trial. Phase 1 and 2 trials show that ciraparantag is an antidote for both heparins and DOAC with a very fast onset of action, no renal clearance and no known drug-drug interactions. None of the currently available anticoagulant antidotes fulfil the criteria of an ideal antidote. Abstract : Despite the improved safety-profile of direct oral anticoagulants (DOACs), bleeding complications remain an important side effect of anticoagulant treatment. Although anticoagulant-specific antidotes are available, an universal anticoagulant reversal agent in case of life-threatening bleeding or emergency surgery is not yet available. Ciraparantag, a synthetic small molecule that inactivates heparins and DOAC, is a promising new reversal agent that has been investigated in phase 2 trials. In this short review we provide an overview of the preclinical and clinical evidence of ciraparantag, and compare strengths and weaknesses of ciraparantag and the currently available anticoagulant reversal strategies.